Salt processing: A unique and classic technology for Chinese medicine processing - Hou, Ajiao; Lv, Jiahao; Zhang, Shihao; Zhang, Jiaxu; Yang, Liu; Jiang, Hai; Kuang, Haixue (Frontiers in Pharmacology, 2023)
Traditional Chinese medicine (TCM) processing is the summary of long-term clinical experience, processing can change the property, taste and meridian of TCM, achieve the purpose of reducing toxicity and increasing efficiency, to ensure the safety of clinical medication. This paper summarizes the research advance of salt processing in recent years from the aspects of the types of excipients, salt processing methods, salt processing purpose and the influence of salt process on the chemical composition, pharmacodynamic effect and in vivo behavior of TCM, and analyzes and discusses the shortcomings of the current research, so as to provide ideas for the further research and development of salt processing of TCM. The results show that salt processing is helpful to introduce drugs into the kidney channel and enhance the effect of nourishing Yin and falling fire. The pharmacological effect, chemical composition and in vivo behavior of TCM will change after salt processing. In the future, we should strengthen the research on standardizing the dosage of excipients, the quality standard after processing, the relationship between the change of chemical composition after salt processing and the enhancement of pharmacological efficacy, so as to deeply explain the principle of salt processing, and further improve and optimize the salt making process. By combing the influence of the of salt processing of TCM and analyzed the current problems, we hope to provide guidance for the in-depth study of the salt processing mechanism of TCM and the inheritance and innovation of TCM processing technology.